(untitled) (Jurnal Pilar Nusa Mandiri, 2022)
The issue of food security is not only the task of farmers, therefore starting to participate in growing vegetables at home through hydroponic techniques can be a solution. Hydroponics is one solution for urban farming or farming activities independently in urban areas in Indonesia. In order to get an abundant harvest on limited land, it requires quality seeds. Good vegetable seeds hold the key to determining a good harvest too. So, you should not carelessly buy vegetable seeds to grow vegetables hydroponically. But the problem is, with so many vegetable seed products for hydroponics on the market, it makes someone confused to choose the right product that suits their needs. The main purpose of this research is to develop a decision support system for selecting hydroponic vegetable seeds with a website-based Exponential Comparison Method to facilitate decision makers in determining the right seeds and according to their needs. The Exponential Comparison method can perform a priority order of decision alternatives on existing criteria and can distinguish the value of each alternative in contrast. The decision support system developed produces calculations using the valid Exponential Comparison Method because the results are in accordance with manual calculations. In addition, based on the black-box testing technique, it shows that the system built has been running well.